Pengaruh Kompetensi dan Disiplin Kerja terhadap Kinerja Pegawai BPJS Kesehatan Kabupaten Pringsewu - Hepiana Patmarina; Nuris Sanida; Moh. Oktaviannur; Satrio Danang Cahyo Harsinto (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Iwn today's ersa, work life prioritizes workers who think far ahead, are smart, innovative, and contemporary. Even in this situation, the position of human resoaurces plsays a vital role in an organization. Institutional, also prioritizes sufficient management aspects when managing the organization. Likewise with BPJS Kesehatan Pringsewu Regency wshich is the object of the author's research. This stsudy used quantitative methods with a sample of 40 respondents. The analytical techniques ssed for this research will test the validity, reliability, and multiple liniear regression analysis. The results of this study are that there is an influence between Competence on Employee Performance 41.69%, then the influence between Work Discipline on Employee Performance is 70.22%, and the variable requirements for Competence and Work DisipIin on Employee Performance is 0.833%. The results of this study are the variable X1 (Competence) and variable X2 (Work Discipline) have a signis.ficant effect on Employee Perfmormance (Y), by % it means that these two variables affect each other and affect each other.